Emerging Metabolic Targets in the Therapy of Hematological Malignancies. (18th August 2013) - Leni, Zaira; Parakkal, Geetha; Arcaro, Alexandre
Abstract : During the last decade, the development of anticancer therapies has focused on targeting neoplastic-related metabolism. Cancer cells display a variety of changes in their metabolism, which enable them to satisfy the high bioenergetic and biosynthetic demands for rapid cell division. One of the crucial alterations is referred to as the "Warburg effect", which involves a metabolic shift from oxidative phosphorylation towards the less efficient glycolysis, independent of the presence of oxygen. Although there are many examples of solid tumors having altered metabolism with high rates of glucose uptake and glycolysis, it was only recently reported that this phenomenon occurs in hematological malignancies. This review presents evidence that targeting the glycolytic pathway at different levels in hematological malignancies can inhibit cancer cell proliferation by restoring normal metabolic conditions. However, to achieve cancer regression, high concentrations of glycolytic inhibitors are used due to limited solubility and biodistribution, which may result in toxicity. Besides using these inhibitors as monotherapies, combinatorial approaches using standard chemotherapeutic agents could display enhanced efficacy at eradicating malignant cells. The identification of the metabolic enzymes critical for hematological cancer cell proliferation and survival appears to be an interesting new approach for the targeted therapy of hematological malignancies.